2022
DOI: 10.1021/acsomega.2c01106
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Electrochemical Sensor Based On an Aminated MIL-101(Cr) MOF for the Detection of Tartrazine

Abstract: The aminated metal–organic framework H 2 N-MIL-101(Cr) was used as the carbon paste electrode (CPE) modifier for the determination of tartrazine (Tz) in soft drinks. The amino material was characterized by electrochemical impedance spectroscopy and showed significantly faster electron transfer with lower charge-transfer resistance (0.13 kΩ) compared to the electrode modified with the unfunctionalized MIL-101(Cr) material (1.1 kΩ). The H 2 N-MIL-101(Cr)-modified CPE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 35 publications
(62 reference statements)
0
15
0
Order By: Relevance
“…Sensors have penetrated into a wide range of fields, such as industrial production [ 181 , 182 , 183 ], environmental protection [ 184 ], bioengineering [ 179 , 185 ], medical diagnosis [ 186 , 187 , 188 , 189 ], marine exploration, and so on. MIL-101(Cr) also had great application value in sensing due to its characteristics [ 190 , 191 ]. Haghighi et al [ 192 ] reported a new quartz gas sensor by using MIL-101(Cr) as a sensing material for the detection of formaldehyde gas in the environment.…”
Section: Applicationsmentioning
confidence: 99%
“…Sensors have penetrated into a wide range of fields, such as industrial production [ 181 , 182 , 183 ], environmental protection [ 184 ], bioengineering [ 179 , 185 ], medical diagnosis [ 186 , 187 , 188 , 189 ], marine exploration, and so on. MIL-101(Cr) also had great application value in sensing due to its characteristics [ 190 , 191 ]. Haghighi et al [ 192 ] reported a new quartz gas sensor by using MIL-101(Cr) as a sensing material for the detection of formaldehyde gas in the environment.…”
Section: Applicationsmentioning
confidence: 99%
“…The study encompassed a range of substances, including nutrients such as iron, manganese, copper, zinc, magnesium, calcium, sugar, and vitamins B1, B6, E, and C, which were found in soft drinks depending on their composition. The sports drinks tested contained fiber, proteins, carbohydrates, salts, preserva- [51] Copyright (2022), under the terms of the CC-BY-NC-ND 4.0 license., b) Cu 2 + modified Zr-based metal-organic framework-CTAB-graphene for sensitive electrochemical detection of SY [53] Copyright (2022), with permission from Elsevier and c) Determination of SY and TZ in drinks using screen-printed carbon electrodes modified with reduced graphene oxide and NiBTC frameworks. [54] Copyright (2020), with permission from Elsevier.…”
Section: Metal Complex and Metal-organic Framework (Mofs)mentioning
confidence: 99%
“…The presence of a large number of multifunctional pores, developed by the organic ligands and metals present, greatly contributes to these benefits. [53][54][55][56][57][58]…”
Section: Metal Complex and Metal-organic Framework (Mofs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with other traditional techniques, electrochemical sensing methods have the advantages of good selectivity, high sensitivity, simple operation, and fast response time [ 7 , 8 , 9 ]. The detection performance of an electrochemical sensor depends on the chemical properties of the modified materials used in the working electrodes [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%